Напрямки вдосконалення діяльності публічних службовців в Україні - Музичук, О. М.; Muzychuk, O. M. (Науковий вісник Дніпропетровського державного університету внутрішніх справ. – 2023. – № 3. – С. 120-126, 2023)
Розглянуто проблематику діяльності публічних службовців в Україні та напрацювання відповідних напрямів вдосконалення законодавства в цій сфері. З урахуванням позицій вітчизняних та закордонних науковців виокремлено новітні напрями вдосконалення діяльності публічних службовців, зокрема: забезпечення високого морально-етичного рівня публічних службовців; підтримання належного рівня фізичної підготовленості та нормального стану здоров’я публічних службовців; підвищення цифрової компетентності публічних службовців тощо. Виокремлено перспективні напрями подальших досліджень з питань вдосконалення діяльності публічних службовців.

The article emphasizes that the activities of public servants include specific areas of implementation of the rights and responsibilities assigned to them, the performance of tasks and functions assigned to subjects of public administration, as well as activities to ensure a comprehensive system of welfare of public servants, their professional development, comprehensive realization as individuals, rest, health, including their family members. Attention is focused on the fact that in the conditions of the latest challenges that have arisen in Ukraine under the conditions of martial law, in particular, the "personnel famine" in the de-occupied territories, the restructuring of the security realities of the activity of public servants, the latest understanding of the ethical and communication component of such activity, there is a need to find the latest directions for its improvement. It is noted that orientation to the needs of the population, the quality of the provided services should not belittle the importance of ensuring a high level of professional well-being of the public servants themselves. At the same time, the elements of such well-being include opportunities provided and guaranteed by the state for the professional and personal development of public servants. It was emphasized that the possibilities of non-formal and informal education, creative collectives based on subjects of public administration, etc., have significant potential in this context. Taking into account the positions of domestic and foreign scientists that we have understood, the latest directions for improving the activities of public servants have been singled out, in particular, ensuring a high moral and ethical level of public servants in Ukraine, maintaining the proper level of physical fitness and normal health of public servants, increasing the digital competence of public servants. On the basis of the directions for improving the activities of public servants in Ukraine, which we have understood, the promising directions for further research include a thorough analysis of the impact of globalization and digitalization on the essence of public service, research into the digital dimension of the activities of public servants in the leading countries of the world, as well as the institutional, functional and normative-legal dimension of the organization of the interaction of public administration subjects with public organizations in the field of physical culture and sports, conducting interdisciplinary medical and legal studies of the influence of specific conditions of professions activities of public servants on the occurrence of certain diseases.

Рассмотрена проблематика деятельности публичных служащих в Украине и наработка соответствующих направлений усовершенствования законодательства в этой сфере. Определены новейшие направления совершенствования деятельности публичных служащих, в частности: обеспечение высокого морально-нравственного уровня публичных служащих; поддержка надлежащего уровня физической подготовленности и нормального состояния здоровья публичных служащих; повышение цифровой компетентности публичных служащих и т.д. Выделены перспективные направления дальнейших исследований по вопросам усовершенствования деятельности публичных служащих.
Directions for improving the activities of public servants in Ukraine
Keywords: публічні службовці; публічне адміністрування; діяльність; професійний добробут; морально-етичний рівень; цифрова компетентність; public servants; public administration; activity; professional welfare; moral and ethical level; digital competence; публичные служащие; публичное администрирование; деятельность; профессиональное благосостояние; морально-нравственный уровень; цифровая компетентность